Clinical pathology of alcohol. Issue 4 (April 1983) - Marks, V
Abstract : There is good though not conclusive evidence that a small to modest average daily intake of alcohol--that is, 20-30 g/day is associated with increased longevity due mainly to a reduction in death from cardiovascular disease. Larger average daily alcohol intakes--especially those in excess of 60 g/day for men and 40 g/day for women--are associated with gradually increasing morbidity and mortality rates from a variety of diseases. Alcohol may be unrecognised as the cause of somatic disease, which can occur without overt psychosocial evidence of alcohol abuse, unless the index of suspicion is high and a thorough drink history obtained. Laboratory tests for the detection and/or confirmation of alcohol abuse are useful but subject to serious limitations being neither as sensitive nor specific as sometimes believed. The value of random blood and/or breath alcohol measurements, in outpatients, as an aid to diagnosis of alcohol-induced organic disease is probably not sufficiently appreciated and, though relatively insensitive, is highly specific.